ANALISIS FAKTOR PENYEBAB PRODUK CACAT DENGAN MENGGUNAKAN METODE SEVEN TOOLS DI PT ADIS DIMENSION FOTWEAR - Pipit Hedlisa; Asep Rahmatullah; Dedy Khaerudin (LPPM Universitas Bina Bangsa, 2021)
The presence of rejected products in the Phylon Injection departement in PT Adis Dimension Footwear is still considered by the negligence of Workers, Methode, Machine, Materials and the Environment that cause company losses because the company must reproduce to replace reject products. The research was conducted to determine and analyze the level of defective products that occurred during 2017 and 2018, find out the highest types of reject, and know the factors causing these defective products. This research was conducted with a case study qualitative approach (descriptive approach). Data collection by conducting interviews, observation, and documentation. Research procedures using the theory of Milles and Huberman. Data validity was done by triangulation. Moreover, Seven Tools is the method in this research. The results of the analysis using the Pareto Diagram of rejecting in 2017 and 2018 were 171.164 pcs, and the highest reject was produced by burning, namely 58.414 pcs, of other types of reject, namely bubbles as many as 47.936 pcs, dirty as many as 37584 pcs, deformed as many as 14.770 pcs, hole as 8513 pcs and tearing as many as 3.947 pcs. The highest reject histogram was burning, which was 112353 pcs, and the Control Chart had p values out of UCL and LCL, which means that the product defect rate exceeded the control limit. Based on the analysis results using the Seven Tools method, it can be concluded that the Seven Tools methode can find out the problems that occur in the company.